Physiologic Considerations of Therapeutic Slideboard Rehabilitation With an External Loading Device - Kimura, Iris F (National Athletic Trainers Association, 2006)
Context: Slideboard exercise is consistent with the American College of Sports Medicine guidelines for exercise intensity of 55% to 90% of maximal heart rate or 40% to 85% of maximal oxygen uptake. Objective: To determine if slideboard exercise while in a leg harness increases the metabolic and cardiorespiratory demands. Design: Repeated-measures design. Setting: Athletic Training Research Laboratory. Patients or Other Participants: Sixteen volunteers from the university community. Intervention(s): Subjects performed 2 graded slideboard exercise tests with and without the leg harness, each 2-minute stage ranging from 46 to 90 slides per minute. Main Outcome Measure(s): We measured maximal oxygen uptake, heart rate, blood lactate, respiratory exchange ratio, ratings of perceived exertion, and total time to exhaustion during each session. Results: Significant decreases in maximal oxygen uptake and blood lactate were observed when the leg harness was used. Conclusions: Performance was hindered when subjects wore the leg harness during the slideboard exercise.